Drivers of mechanical performance variance in 3D‐printed fused filament fabrication parts: An Onyx FR case study. Issue 9 (28th June 2021) - Ma, Christine; Faust, Jessica; Roy‐Mayhew, Joseph D.
Abstract: Effects on mechanical properties of user‐controlled and user‐uncontrolled factors in a 3D printing system were investigated using a flame retardant carbon fiber reinforced nylon filament. Moisture and print orientation, both user controllable elements, dominated mechanical property variation. Dry samples exhibited tensile (flexural) strength 2.4 (2.1) times greater than that of wet samples, while ZX samples were measured to have about half the tensile strength of XY and XZ samples. User‐uncontrolled factors including material to material variation and printer to printer variation were found to have minor impact (<5%) on part tensile strength. Reinforcing the part with 21 vol% continuous fiber lowers the moisture induced variance from 13% to 2% in addition to increasing the measured strength by about 10× (to 451 MPa). Abstract : Effects on mechanical properties of user‐controlled and user‐uncontrolled factors in a 3D printing system using a flame retardant carbon fiber reinforced nylon filament were investigated. Moisture and print orientation, both user controllable elements, dominated mechanical property variation.